Henry hikes to Fitchburg - Johnson, D. B. 1944- (Houghton Mifflin, 2000)
While his friend works hard to earn the train fare to Fitchburg, a bear, modeled on a young Henry Thoreau, walks the thirty miles through woods and fields, enjoying nature and the time to think great thoughts. Includes biographical information about Thoreau.